Analisis Kepuasan Pengunjung terhadap Layanan Objek Wisata Tebing Suban, Kabupaten Rejang Lebong - Ririn Nurhalizah; Dwita Prisdinawati; Mira Yanuarti; Dodi Aprianto (Lembaga Pengembangan Kinerja Dosen, 2025)
This research was conducted in February-April 2025 at the Tebing Suban Tourism, Talang Ulu Village, East Curup, Selupu Rejang District, Rejang Lebong Regency. So the purpose of this study was to determine visitor satisfaction with the services of the Tebing Suban tourist attraction, Rejang Lebong Regency. The method used in this sampling was by Accidental Sampling, a sampling technique based on coincidence, namely anyone who accidentally meets the researcher can be used as a sample, if it is considered that the person who happened to be met is suitable as a data source. The data analysis method used is quantitative descriptive and data processing is carried out using the help of the SPSS (Statistical Program for Social Science) and Microsoft Excel applications which are presented in the form of tables and tabulations, then data measurements are carried out with visitor satisfaction tools, namely Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). the results of the research that has been done, then several conclusions can be drawn, namely the results of the Importance Performance Analysis (IPA) based on the Cartesian diagram show that of the 20 service performance attributes of the Tebing Suban Tourism Object, there are 5 attributes that are considered very important and are the main priority in determining visitor satisfaction. Based on the calculation of the Customer Satisfaction Index (CSI), the satisfaction index value is 79.36%. This value is obtained from the Weighted Score divided by the Likert Scale value range.